Interrogation techniques focused on perceptions of inclusion in physical education (review study) - Ladislav Baloun; Hana Válková (Tělesná Kultura, 2017)
Background: The purpose of this article is to build on the systematic exploration of the attitudes of teachers, students of physical education and intact pupils toward inclusion process at primary schools in Czech. These studies were conducted at Faculty of Physical Culture in Olomouc since the 90s of the 20th century. Objective: Summarization of the characteristics of the questionnaires which find attitudes in relation toward inclusion in physical education. Description of results of bachelor and master theses which were conducted on Faculty of Physical Culture. Methods: Analysis of document (bachelor and master theses of students of Faculty of Physical Culture) was used for data collection. All thesis in which was worked with attitude scales PEATH, ATIPDPE or CAIPE-CZ were included to the study. Thesis were found in the electronic catalogues of the Library of Palacký University in Olomouc on April 2014. We used six keywords - integration, physical education, attitudes, ATIPDPE, CAIPE, PEATH. Results: We included 20 theses to the study (4 bachelors and 16 masters). ATIPDPE scale was administered in 7 theses (2 bachelors and 5 masters), CAIPE-CZ was administered in 10 theses (2 bachelor and 8 master), PEATH scale was administered in 3 master theses. Conclusions: This review study supported the contact theory, which says that opinions or attitudes could be influenced only in contact with the real situation.